Preliminary paleomagnetic results from the Carboniferous-Permian El Imperial Formation sedimentary rocks in the San Rafael Block, Mendoza province - Tomezzoli, R.N. (2006)
During the Early Permian an extensive deformation belt well-known as Gondwánides developed in the southwest Gondwana margin. A foreland basin has been settled during the Late Carboniferous - Early Permian in the western end of this strip, and is represented by the El Imperial Formation, which crops out in the San Rafael Block. The upper section of this unit records an inversion of the ancient slopes, which has been interpreted as the first evidence of the migration of the orogenic front towards the foreland. Therefore, a paleomagnetic study has been carried out on this unit, searching for elements that allow to constraint the deformation age to evaluate the possible diachronism of it. First paleomagnetic results obtained in EI Imperial Formation, from the lower member in the Represa Agua del Toro and from the upper member in the Puesto La Josefa, are presented and discussed. These rocks have reverse magnetizations carried by hematite, of possible Permian age. Pole positions are discordant with the apparent polar wander path from South America. These differences could be explained because: secular variation was not properly averaged; rotations about vertical axes of the sampling localities; or the combination of these factors. © 2006 Asociación Geológica Argentina.